Phase transition and dielectric properties of B2O3doped BZT ceramics - P. Jarupoom (2018)
In the present work, effects of B2O3(a flux addition) on phase transition behaviour and dielectric properties of BZT ceramics were investigated. The ceramics were prepared by a solid state sintering method. Properties of the ceramics were characterized by X-ray diffraction, electron microscopy, and dielectric measurement. The dielectric measurement showed that the ferroelectric phase transition of the ceramics became broader and phase transition temperatures increased as the amount of B2O3increased. The results also suggested that boron ions were introduced into the lattice and altered the phase transition characteristics of the ceramics. © 2009 American Institute of Physics.